2010
DOI: 10.1186/1475-2859-9-85
|View full text |Cite
|
Sign up to set email alerts
|

Production of gamma-aminobutyric acid by Lactobacillus brevis NCL912 using fed-batch fermentation

Abstract: BackgroundGamma-aminobutyric acid is a major inhibitory neurotransmitter in mammalian brains, and has several well-known physiological functions. Lactic acid bacteria possess special physiological activities and are generally regarded as safe. Therefore, using lactic acid bacteria as cell factories for gamma-aminobutyric acid production is a fascinating project and opens up a vast range of prospects for making use of GABA and LAB. We previously screened a high GABA-producer Lactobacillus brevis NCL912 and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(164 citation statements)
references
References 37 publications
(46 reference statements)
9
152
0
3
Order By: Relevance
“…In China, it was reported that 1,000 mM levels of GABA has been produced by fed-batch recently (Li et al, 2010). Accordingly, the production of GABA has been increased by screening of a new strain and optimization of fermentation conditions, and the various applications of purposes are possible.…”
Section: Gaba-producing Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In China, it was reported that 1,000 mM levels of GABA has been produced by fed-batch recently (Li et al, 2010). Accordingly, the production of GABA has been increased by screening of a new strain and optimization of fermentation conditions, and the various applications of purposes are possible.…”
Section: Gaba-producing Capabilitymentioning
confidence: 99%
“…It succeeded to produce 1005.8 mM of GABA from 3.1 M MSG by Lb. brevis NCL912 isolated from Paochai in China (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fed-batch fermentation mode, where one or more nutrient is being supplied throughout cultivation (Moulton 2014), can be done in a controllable and reproducible fashion only in bioreactors. These properties make bioreactors a suitable stage for optimization of cultivation conditions, often leading to significant improvements in production yields (Hujanen et al 2001;Ratnam et al 2003;Li et al 2010;Rani and Appaiah 2011).…”
Section: Optimization Of Phenolic Production By Fermentation and Scalmentioning
confidence: 99%
“…GABA, which was originally identified in traditional fermented foods such as cheese, yogurt [5] and kimchi [6], is synthesized through the alphadecarboxylation of L-glutamate catalyzed by glutamate decarboxylase (GAD, EC 4.1.1.15) [2]. GABA is produced by lactic acid bacteria (LABs) such as Lactobacillus paracasei [7], L. buchneri [6], and L. brevis [8,9] (Table 2), and the latter produces high yields of GABA through fedbatch processes [10].…”
Section: Gabamentioning
confidence: 99%